Current advances in the development of meniscus tissue engineering: narrative review - Tong, Jia Bei; Rampal, Sanjiv; Elderdery, Abozer; Wu, Xiaoyun; Ramasamy, Rajesh; Subbiah, Suresh Kumar; Mok, Pooi Ling (Malaysian Medical Association, 2023)
Introduction: The meniscus plays an important role in maintaining homeostasis to facilitate the normal function of the knee joint. It is one of the most commonly injured areas of the knee joint. Meniscal-related injuries can lead to significantly decreased athletic ability, and their incidence has increased yearly. It has been found that most meniscal injuries are irreparable, and meniscectomy can increase the predisposition to knee osteoarthritis. Tissue engineering technology on meniscus repairing and transplantation has received widespread attention recently. This review aimed to analyse the scientific literature regarding the potential applications of tissue engineering on meniscus repairing and transplantation procedures. Method and Materials: The electronic search was carried out using PubMed/MEDLINEⓇdatabases with the keywords “tissue engineering AND meniscus” spanning the period of publications from Jan 1980 until Dec 2022. Results: The literature search identified 405 references in PubMed/MEDLINE, and 179 were selected following the eligibility requirements. The research analysis showed that the existing meniscal tissue engineering studies used a wide variety of seed cells, cytokines, bioactive materials and 3D structures. Each showed distinct advantages and disadvantages in terms of biocompatibility, degradability, mechanical strength, porosity, and etc. It was noted that 3D printing technology is promising for tissue engineering meniscus research. In addition, the optimal use of compression and hydrostatic pressure to markedly improve the functional properties of tissue-engineering meniscal can serve as an useful strategy. Conclusion: This review analysed the different approaches employed for meniscus tissue engineering and regeneration. Meniscal tissue engineering still faces several major challenges in terms of seed cells, choice of materials and 3D printing strategies, which should be effectively overcome to harness the full potential of this technology.